Bali Governor Regulation Number 47 of 2019 Concering The Authority of The Denpasar City Government in Waste Management - Yusuf, Dedi; Rahmasari, Betha (Muhammadiyah Law Review Journal, 2025)
The Bali Governor's Decree No. 381/03-P/HK/2021 and the Governor's Instruction No. 8324 of 2021 regarding Source-Based Waste Management are follow-up steps to the Governor's Regulation No. 47 of 2019. This policy aims to support the vision of "Nangun Sat Kerthi Loka Bali" in preserving environmental sanctity and ensuring public welfare. Waste management in Denpasar is governed by Regional Regulations No. 3 of 2015 and No. 8 of 2023. This research adopts a normative juridical approach through literature review and empirical juridical studies related to Bali Governor Regulation No. 47/2019. Significant challenges remain, such as low community participation, insufficient facilities, and suboptimal coordination. The proposed solutions include socialization, optimizing TPS 3R, source-based management, and the 3R strategy (Reduce, Reuse, Recycle). Law enforcement and the utilization of technology are also crucial for the success of this policy. With a large population and a daily waste volume of 800-900 tons, community participation is essential in creating a healthy and sustainable environment.